2008
DOI: 10.1007/s12217-008-9072-x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Wave Propagation in a Gel-type Belousov–Zhabothinsky Reaction under Micro-gravity

Abstract: The Belousov-Zhabothinsky (BZ) reaction is a chemical reaction which exhibits spatial as well as temporal pattern formation. Being an excitable medium, it can be influenced by even small external forces. One of these small forces which under ground conditions permanently is given is gravity. The gravity dependence of the BZ-reaction has been investigated in some detail up to now, and it has been found that especially the propagation velocity of waves in thin layers of fluid BZ-medium depends significantly on g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…In previous experiments (Nagypal et al 1986;Fujieda et al 1997Fujieda et al , 2002Wiedemann et al 2002;Hanke et al 2009) it has been shown that wave propagation in BZsystems is depending on gravity as well in fluid as in gel systems. This interaction can be attributed to diffusion, convection and buoyancy going on in such systems at different degrees.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In previous experiments (Nagypal et al 1986;Fujieda et al 1997Fujieda et al , 2002Wiedemann et al 2002;Hanke et al 2009) it has been shown that wave propagation in BZsystems is depending on gravity as well in fluid as in gel systems. This interaction can be attributed to diffusion, convection and buoyancy going on in such systems at different degrees.…”
Section: Discussionmentioning
confidence: 95%
“…1a) and than in the A-300. Some more details of a similar set-up have been published previously (Hanke et al 2009). The experiment was switched on after the airplane had reached its cruising altitude, typically about 30 to 60 min after filling the chambers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chemical waves in BZ gels have been widely studied in recent decades. It was found that these waves can be regulated via asymmetry, and chemical oscillations in heterogeneous BZ gels can be controlled via mechanical strain . In addition, BZ gels can sense external mechanical forces to trigger chemical waves …”
Section: Introductionmentioning
confidence: 99%
“…Many other examples of excitable media exist in nature, including wild fires [3], certain living tissues (e.g. the heart [4], esophagus [5], intestine [6] and nerves [7]), chemical reactions [8,9], and more [10]. However, a man-made artificial excitable medium has never before been created.…”
Section: Introductionmentioning
confidence: 99%